The Nature of Data Center Traffic: Measurements and Analysis - Kandula, Srikanth; Sengupta, Sudipta; Greenberg, Albert; Patel, Parveen; Chaiken, Ronnie (2009 Internet Measurement Conference, 2009)
We explore the nature of trac in data centers, designed to support the mining of massive data sets. We instrument the servers to collect socket-level logs, with negligible performance impact. In a 1500 server operational cluster, we thus amass roughly a petabyte of measurements over two months, from which we obtain and report detailed views of trac and congestion conditions and patterns. We further consider whether tracmatrices in the clustermight be obtained instead via tomographic inference from coarser-grained counter data.